2011
DOI: 10.1007/s10858-011-9596-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous acquisition of 13Cα–15N and 1H–15N–15N sequential correlations in proteins: application of dual receivers in 3D HNN

Abstract: We describe here, adaptation of the HNN pulse sequence for multiple nuclei detection using two independent receivers by utilizing the detectable (13)C(α) transverse magnetization which was otherwise dephased out in the conventional HNN experiment. It enables acquisition of 2D (13)C(α)-(15)N sequential correlations along with the standard 3D (15)N-(15)N-(1)H correlations, which provides directionality to sequential walk in HNN, on one hand, and enhances the speed of backbone assignment, on the other. We foresee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11] Following the introduction of parallel NMR spectroscopy, it was shown that one of its main advantages results from its use to collect two or more different kinds of multidimensional correlation experiments, within the time duration that would normally entail to collect a single spectrum. [5][6][7] These "parallel acquisition NMR, all-in-one combination of experimental applications" (PANACEA) strategies, have since been extended to systems of various heteronuclei [8,9] and adapted to protein liquid-state [10,11] and solid-state NMR experiments. [5][6][7] These "parallel acquisition NMR, all-in-one combination of experimental applications" (PANACEA) strategies, have since been extended to systems of various heteronuclei [8,9] and adapted to protein liquid-state [10,11] and solid-state NMR experiments.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Following the introduction of parallel NMR spectroscopy, it was shown that one of its main advantages results from its use to collect two or more different kinds of multidimensional correlation experiments, within the time duration that would normally entail to collect a single spectrum. [5][6][7] These "parallel acquisition NMR, all-in-one combination of experimental applications" (PANACEA) strategies, have since been extended to systems of various heteronuclei [8,9] and adapted to protein liquid-state [10,11] and solid-state NMR experiments. [5][6][7] These "parallel acquisition NMR, all-in-one combination of experimental applications" (PANACEA) strategies, have since been extended to systems of various heteronuclei [8,9] and adapted to protein liquid-state [10,11] and solid-state NMR experiments.…”
mentioning
confidence: 99%
“…More recently, the afterglow phenomenon exploited by Kay and co-workers opened up the possibility for the acquisition of multidimensional NMR spectra of proteins in parallel [39]. The latter approach has been implemented with either one or multiple receivers [40-42]. Sensitivity enhanced experiments in solids have also been proposed by Tycko and co-workers [43] and been implemented in a manner similar to the sensitivity enhancement for solution NMR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth pointing out that, unlike the INEPT procedure, the application of band‐selective 15 N‐ 13 C α HEHAHA mixing sequence for transferring the 15 N i magnetisation to the adjacent “ i +1” and “ i −1” residues makes it possible to conveniently extract the side chain chemical shift information simultaneously. The pulse sequences can also be adapted, using dual receivers as in earlier studies to acquire simultaneously RN[N‐CA HEHAHA]NCO and RN[N‐CA HEHAHA]CAHA correlation data sets. Another approach to simultaneously extract the side chain chemical shifts, using only a single data acquisition, would be to implement RF pulse schemes starting with the excitation of side chain protons such as the HSCSCACON[N‐CA HEHAHA]NH experiment involving the 1 H sc → 13 C sc → 13 C α magnetisation transfer pathway and chemical shift labelling of the side chain resonances in the indirect dimensions (see SI).…”
Section: Figurementioning
confidence: 99%